The Effect of Leadership, Motivation, Communication of Personnel Performance in Banten Police Institutions - Badri Hasan; Ruddi Kurniawan; Iis Istiharoh; John Chaidir; Haerofiatna Haerofiatna; Dika Hilaldi; Ali Imron (Program Studi Ilmu Administrasi Negara FISIP UMRAH, 2026)
This study examines the influence of leadership, work motivation, and organizational communication on personnel performance within the Banten Regional Police. Personnel performance is a crucial factor in police institutions because it is directly related to public service quality, law enforcement effectiveness, discipline, and institutional accountability. The study was motivated by several organizational phenomena, including issues of personnel discipline, work commitment, and the need to strengthen police performance in responding to increasing public demands. This research employed a quantitative approach using a survey method. The population consisted of 3,040 personnel of the Banten Regional Police, while the sample was determined using the Slovin formula with a 10% margin of error, resulting in 97 respondents. Primary data were collected through structured questionnaires using a five-point Likert scale, while secondary data were obtained from relevant literature and organizational documents. Data were analyzed using SPSS through reliability testing, classical assumption testing, multiple linear regression analysis, coefficient of determination, and hypothesis testing. The results show that leadership, work motivation, and organizational communication positively influence personnel performance. The regression equation indicates that all independent variables have positive coefficients, with organizational communication showing the strongest effect compared to leadership and work motivation. The coefficient of determination shows that leadership, work motivation, and communication simultaneously explain 65.8% of the variation in personnel performance, while the remaining 34.2% is influenced by other factors outside this study. These findings indicate that improving personnel performance in police institutions requires an integrated human resource management strategy through stronger leadership, increased motivation, and more effective organizational communication.